Legacies. The complete first season. [videorecording (DVD)] - Russell, Danielle Rose; Shahghasemi, Aria; Bryant, Kaylee; Davis, Matthew, 1978- (Warner archives., 2019)
The next generation of supernatural beings at The Salvatore School for the Young and Gifted is where Klaus Mikaelson's daughter, seventeen-year-old Hope Mikaelson, a tribrid daughter of a Vampire/Werewolf hybrid; Alaric Saltzman's twins, Lizzie and Josie Saltzman; and other young adults, come of age in the most unconventional way possible, nurtured to be their best selves, in spite of their worst impulses. Will these young witches, vampires, and werewolves become the heroes they want to be, or the villains they were born to be?